A putative small solute transporter is responsible for the secretion of G377 and TRAP-containing secretory vesicles during plasmodium gamete egress and sporozoite motility - Kehrer, Jessica; Singer, Mirko; Lemgruber, Leandro; Silva, Patrícia A. G. C.; Frischknecht, Friedrich; Mair, Gunnar R. (PLoS pathogens, 2016)
Regulated protein secretion is required for malaria parasite life cycle progression and transmission between the mammalian host and mosquito vector. During transmission from the host to the vector, exocytosis of highly specialised secretory vesicles, such as osmiophilic bodies, is key to the dissolution of the red blood cell and parasitophorous vacuole membranes enabling gamete egress. The positioning of adhesins from the TRAP family, from micronemes to the sporozoite surface, is essential for gliding motility of the parasite and transmission from mosquito to mammalian host. Here we identify a conserved role for the putative pantothenate transporter PAT in Plasmodium berghei in vesicle fusion of two distinct classes of vesicles in gametocytes and sporozoites. PAT is a membrane component of osmiophilic bodies in gametocytes and micronemes in sporozoites. Despite normal formation and trafficking of osmiophilic bodies to the cell surface upon activation, PAT-deficient gametes fail to discharge their contents, remain intraerythrocytic and unavailable for fertilisation and further development in the mosquito. Sporozoites lacking PAT fail to secrete TRAP, are immotile and thus unable to infect the subsequent rodent host. Thus, P. berghei PAT appears to regulate exocytosis in two distinct populations of vesicles in two different life cycle forms rather than acting as pantothenic transporter during parasite transmission.
Gesehen am 11.05.2020